2021
DOI: 10.3390/ijgi10100668
|View full text |Cite
|
Sign up to set email alerts
|

To Drive or to Be Driven? The Impact of Autopilot, Navigation System, and Printed Maps on Driver’s Cognitive Workload and Spatial Knowledge

Abstract: The technical advances in navigation systems should enhance the driving experience, supporting drivers’ spatial decision making and learning in less familiar or unfamiliar environments. Furthermore, autonomous driving systems are expected to take over navigation and driving in the near future. Yet, previous studies pointed at a still unresolved gap between environmental exploration using topographical maps and technical navigation means. Less is known about the impact of the autonomous system on the driver’s s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…On a theoretical level, whilst several theories have postulated as to why eNA technology reduces survey knowledge acquired from the environment, including reduced cognitive load, divided attention, and reduced time to process environmental features due to increased velocity (30,31), the present study provides a potential explanation that survey knowledge is reduced due to spatial learning strategy, as we show that drivers who use eNA for everyday journeys to new locations were less likely to use landmark-dependent navigation strategies.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…On a theoretical level, whilst several theories have postulated as to why eNA technology reduces survey knowledge acquired from the environment, including reduced cognitive load, divided attention, and reduced time to process environmental features due to increased velocity (30,31), the present study provides a potential explanation that survey knowledge is reduced due to spatial learning strategy, as we show that drivers who use eNA for everyday journeys to new locations were less likely to use landmark-dependent navigation strategies.…”
Section: Discussionmentioning
confidence: 56%
“…Previous experimental studies, conducted amongst younger populations, have found that driving whilst using eNA is associated with impairments to route learning (29,30). Therefore, whilst greater eNA usage may not impair objective cognitive facets overall, they may impair learning of spatial environments to which they are applied.…”
Section: Discussionmentioning
confidence: 98%
“…Under the increasing level of automation available in production vehicles, continuous driver monitoring becomes a crucial safety factor [ 1 ]. To ensure drivers remain undistracted in the driving loop [ 2 ] and to prevent a negative impact of the autonomous system on the ability of drivers to take over [ 3 , 4 , 5 ], multiple methods from various research fields including human–machine interaction, psychology, computer science, and ergonomics have been investigated. Thus, in-cabin driver monitoring cameras [ 6 , 7 ] and eye-tracking systems were tested [ 3 , 8 , 9 , 10 , 11 , 12 ] and partly integrated into production vehicles.…”
Section: Introductionmentioning
confidence: 99%